Myocardial impairment in rheumatoid arthritis patients with normal left ventricular function: findings from speckle tracking echocardiography - Dhahri, Rim; Houaida, Mahfoudhi; Dergaa, Ismail; Ben Ammar, Lobna; Ceylan, Halil İbrahim; Ben Abderrazek, Youssef; Fenniche, Insaf; Chenik, Sarra; Fehri, Wafa; Muntean, Raul Ioan; Gharsallah, Imène (Frontiers in Medicine, 2025)
BackgroundRheumatoid arthritis (RA) is a chronic inflammatory condition recognized for elevating cardiovascular morbidity and mortality, even in the absence of overt cardiovascular symptoms. Traditional echocardiogram frequently overlooks early myocardial failure, necessitating more sensitive imaging modalities, such as speckle tracking echocardiography (STE), to effectively diagnose subclinical left ventricular systolic dysfunction (LVSD). Timely identification of cardiac involvement is essential for reducing long-term cardiovascular risks in people with rheumatoid arthritis.ObjectivesThis study sought to (i) determine if STE can identify subclinical myocardial dysfunction in RA Patients with normal left ventricular function as assessed by transthoracic echocardiography and (ii) identify clinical and biological factors linked to this extra-articular manifestation.MethodsA total of 36 RA patients and 36 matching healthy controls were included. All subjects underwent standard transthoracic echocardiogram and speckle tracking STE to evaluate left ventricular function. Global longitudinal strain (GLS) was employed to identify subclinical left ventricular systolic dysfunction, with a GLS threshold of ≤ − 18% signifying LVSD. Clinical and biochemical variables, such as hemoglobin concentrations, diabetes mellitus, and disease activity (DAS28-CRP), were evaluated to determine their correlation with compromised myocardial strain.ResultsRA patients had a significantly diminished GLS compared to healthy controls (18.99 ± 2.81% vs. 20.42 ± 1.33%, p = 0.015), notwithstanding a normal left ventricular ejection fraction (LVEF). Subclinical LVSD was detected in 33% of RA patients, but none of the control subjects exhibited this condition. Anemia was identified as the most significant independent predictor of diminished GLS (OR: 11.39, 95% CI: 1.57–82.89, p = 0.016), although diabetes mellitus and age exhibited associations with myocardial strain in univariate analysis. No substantial correlations were identified between GLS and disease activity (DAS28-CRP) or immunological markers (RF, anti-CCP).ConclusionSTE identified subclinical LVSD in a significant number of RA patients with normal LVEF, emphasizing its effectiveness in early cardiovascular risk assessment. Hemoglobin levels were a crucial predictor of subclinical LVSD, highlighting the necessity of thorough cardiovascular risk evaluations in RA, especially for individuals with anemia or other concomitant conditions. Incorporating STE into standard assessments may facilitate early interventions and enhance long-term cardiovascular outcomes for patients with RA.